Food in a changing climate - Mann, Alana (SocietyNow., 2021)
Our diets are going to change dramatically as global warming affects growing seasons and the availability of different foods around the world. Meanwhile, our foodways are among the biggest contributors to greenhouse gas emissions. To address these challenges Food in a Changing Climate demands we look beyond our plates to the roots of inequity in our food systems. It presents an unashamedly political agenda for 'deep adaptation', focused on the rejuvenation and strengthening of local and regional food systems that have been steadily eroded in the name of economic efficiency. The colonial origins of fossil-fuel based food production and trade persist in the marginalisation of farmers, food workers, and fishers in a corporatized food system that promotes the exploitation of the environment, excess production, and hyper-consumerism. These factors contribute to climate change, poverty, and health inequities on a global scale. Drawing on case studies from around the world, this book illustrates how the commodification of food has made us particularly vulnerable to climate change, extreme weather events, and pandemics such as COVID19. These shocks reveal the danger of our reliance on increasingly complex supply chains - dominated by a decreasing number of mega-companies - for our food security. The unsustainability of the way we produce and eat food is clear. It has been for a long time. Food in a Changing Climate explores how we can cultivate resilient communities through the just application of new technologies, the recovery of traditional knowledges, and by building diversity to protect the livelihoods of food producers everywhere.